2012
DOI: 10.1177/0734282912440787
|View full text |Cite
|
Sign up to set email alerts
|

Variance in Broad Reading Accounted for by Measures of Reading Speed Embedded Within Maze and Comprehension Rate Measures

Abstract: Maze and reading comprehension rate measures are calculated by using measures of reading speed and measures of accuracy (i.e., correctly selected words or answers). In sixth-and seventhgrade samples, we found that the measures of reading speed embedded within our Maze measures accounted for 50% and 39% of broad reading score (BRS) variance, respectively. Combining reading speed with Maze accuracy to form Maze rate increased explained BRS variance by <2%. For our comprehension measures, reading speed accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…() recommended using a combined ORF and Maze indicator. Others have recommended using a Maze accurate response rate rather than a raw Maze score (Hale, Skinner, Wilhoit, Ciancio, & Morrow, ; McCane‐Bowling, Strait, Guess, Wiedo, & Muncie, ). Hence, we acknowledge that the results reported in this study may have been a function of using particular AIMSweb passages in particular grades and the separated WRC for the ORF and raw score for the Maze measure.…”
Section: Discussionmentioning
confidence: 99%
“…() recommended using a combined ORF and Maze indicator. Others have recommended using a Maze accurate response rate rather than a raw Maze score (Hale, Skinner, Wilhoit, Ciancio, & Morrow, ; McCane‐Bowling, Strait, Guess, Wiedo, & Muncie, ). Hence, we acknowledge that the results reported in this study may have been a function of using particular AIMSweb passages in particular grades and the separated WRC for the ORF and raw score for the Maze measure.…”
Section: Discussionmentioning
confidence: 99%
“…CBMs are typically timed (e.g., number of words read correctly in 1 min, number of words retold from an orally read passage within a specified time). Researchers have investigated the effect that time, conceptualized as rate or speed, has on the student's overall performance (Hale, Skinner, Wilhoit, Ciancio, & Morrow, 2012;Neddenriep, Skinner, Hale, Oliver, & Winn, 2007;Skinner, Neddenriep, Bradley-Klug, & Ziemann, 2002;Skinner et al, 2009;Williams et al, 2011). Based on data from these studies, Skinner and colleagues concluded that reading speed is highly correlated to performance on standardized measures (i.e., Woodcock-Johnson Test of Achievement [WJ-III], Broad Reading Cluster, and Tennessee Comprehensive Assessment Program [TCAP] Reading Composite) and is a stronger predictor of overall reading ability than brief reading comprehension measures.…”
Section: Cbm Within Rti Modelsmentioning
confidence: 99%
“…However, results from other studies appear to be inconsistent with this result. For example, Hale et al (2012), Neddenriep et al (2007), Skinner et al (2002), Skinner et al (2009), and Williams et al (2011) found that reading speed was the strongest predictor of overall reading ability, and concluded that rate was highly correlated to both reading fluency and reading comprehension performance on standardized achievement measures (i.e., WJ-III, Broad Reading Cluster, and TCAP reading composite). MIR:R is timed, but the Comprehension Percentage score is not overtly impacted by time; that is, a student who reads very slowly and attempts to read only five ideas in 3 min achieves 100% comprehension if he or she correctly identifies those five ideas.…”
Section: Relations Between the Mir:r Composite Score And Tcapmentioning
confidence: 99%